Associated factors in Streptococcus bovis bacteremia and colorectal cancer. Issue 4 (26th April 2016) - Tsai, Cheng‐En; Chiu, Cheng‐Tang; Rayner, Christopher K.; Wu, Keng‐Liang; Chiu, Yi‐Chun; Hu, Ming‐Luen; Chuah, Seng‐Kee; Tai, Wei‐Chen; Liang, Chih‐Ming; Wang, Hsin‐Ming
Abstract: Reports suggest that between 25% and 80% of patients with Streptococcus bovis / gallolyticus bacteremia have concomitant colorectal tumors. This retrospective study was aimed to identify associations between clinical characteristics and a finding of colorectal neoplasm in patients with S. bovis bacteremia who had colonoscopy examination. We retrospectively reviewed the records of patients with S. bovis bacteremia from Kaohsiung Chang Gung Memorial Hospital, Kaohsiung, Taiwan, between January 2004 and January 2014. Clinical data including age, sex, comorbidities, blood culture, and colonoscopy findings were collected and their relationship to a finding of colorectal cancer was examined. A total of 107 patients with S. bovis bacteremia were identified, of whom 49 (72% male; age 65 ± 12 years) were investigated with colonoscopy; 15 of these patients (30.6%) had colorectal adenocarcinoma. Female sex ( p  = 0.014) and a history of noncolorectal malignancy ( p  = 0.004) were associated with a finding of colorectal adenocarcinoma. There were no associations with age, percentage of blood cultures, or the presence of diabetes mellitus, chronic liver disease, heart disease, or end‐stage renal disease. Our results show that S. bovis bacteremia is associated with the presence of colorectal adenocarcinoma, especially in female patients, and concomitant existence of other malignancies.